Combined effects of climate and fire‐driven vegetation change constrain the distributions of forest vertebrates during the 21st century. (19th January 2022) - Hoecker, Tyler J.; Turner, Monica G.
Abstract: Aim: Biodiversity conservation relies in part on enduring habitat in protected areas. In fire‐prone ecosystems, shifts in species' ranges will result both from changes in climate and fire‐catalysed vegetation change, which could lead to niche contraction and undermine protected‐area efficacy. We explored these dynamics for three forest species with varied niches representative of other taxa and different hypothesized responses to fire‐regime change (black‐backed woodpecker, Picoides arcticus ; North American marten, Martes spp.; and red squirrel, Tamiasciurus hudsonicus ). We asked: How do the extent and spatial pattern of these species' distributions change during the 21st century based on the independent and joint effects of climate and vegetation? Location: Greater Yellowstone Ecosystem (Wyoming, USA). Methods: For each species, we developed separate distribution models based on climate and forest attributes, projected under four climate‐fire scenarios (a 2 × 2 design with moderate and high temperature and precipitation change). A spatially explicit forest landscape model calibrated for Greater Yellowstone was used to project fire and forest dynamics through 2100, and climate suitability was estimated with MaxEnt. Results: Suitable habitat for all three species based on climate or vegetation alone frequently did not overlap on the landscape, and habitat patches became simpler in shape and farther apart. Climatically suitable habitat for the black‐backed woodpecker increased in all scenarios, and suitable forest structure expanded by a factor of 30 in dry scenarios with more fire. Climatically suitable habitat for martens declined with warming and drying; the area of suitable vegetation fell >80% with fire‐driven losses of mature forest. Red squirrel habitat was maintained in all scenarios, but was sensitive to aridity, and patches were redistributed and compacted. Main conclusions: Projections based on climate alone may misrepresent future species distributions, especially where disturbances accelerate vegetation change. Our results identify important consequences of fire‐regime change for wildlife in forests dominated by obligate‐seeder or fire‐sensitive conifers.